Zwischen Utopie und Zensur – Platonovs Prosa der Kriegsjahre - Hodel, Robert (Wiener Slawistischer Almanach, 2022)
For Platonov, the war deaths, which he witnessed as a correspondent in the Red Army, coincided with the death of his son who had been released from the GULAG in 1941 with tuberculosis and died a year later. The writer tried to make sense of both tragedies in the hope that the remembrance of the dead would become the foundation of a new, communal life. When in 1943 the Writers’ Union issued a slogan calling for a greater recognition of the role of officers and communist leaders in the press and literature, Platonov’s idea of a community of independent individuals, which had preoccupied him since Chevengur, came under increasing attack. This also put an end to his hopes for a new state before the end of the war.